THEOREM OF BOREL TYPE FOR WHOLE ROWS DIRIHLE WITH ARBITRARY COMPLEX SEQUENCE OF INDEXES - Овчар, Ігор Євгенійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In this article a Borel's type relation $\ln |F(z)|\le (1+o(1)) \ln μ (z,F),$ where $z→∞$ $(z\inK\E)$ between logarithms of maximum of the modulus of its sum and a maximal term of entire Dirichlet series with arbitrary sequence of complex exponents $λ_n$ is obtained.